VERBAL INTERACTION BETWEEN TEACHER AND STUDENTS IN THE CLASSROOM - Susie Kusumayanthi; Lia Riyani Nuroniah (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2020)
This research was conducted in the tenth grade students in a senior high school in Bandung Barat. The purposes of this study are to identify the types of verbal interaction in the classroom based on Flanders Interaction Analysis Categories (FIAC) and what is the impact to students’ speaking skill. This research used descriptive qualitative method. More specifically this research was classified as a case study. The instruments of this research used observation and interview. The data from observations were accompanied by Video recording. Then, transcribed into the written form. Observation data were processed into FIAC sheet and calculated to find the dominant type. Interview data were processed using descriptive qualitative. The findings of the research show that all types of verbal interaction based on Flanders Interaction Analysis Categories (FIAC) were used by the teacher and students in the classroom. The type most often used is asking questions and student talk responses with a percentage of 26.34% at the first meeting and 22.12% at the second meeting. Then the students' talk response with a percentage of 28.14% at the first meeting and 34.62% at the second meeting. The results of the research with interviews stated that verbal interaction can help students develop a little in English speaking skills, especially on elements of pronciation, grammar and vocabulary.